Identify the Most Important Skill Tests for the Selection of Handball Players Juniors - Sabeeh Mustafa, Usama (International Journal of Psychosocial Rehabilitation, 2020)
Reaching the global sport stage calls for, from the start, a great practice method for long periods because the hero does not generate between day and night, and this education procedure is associated with many elements to attain the desired outcomes, and the first of these factors is an appropriate method inside the choice, so the choice technique ought to be issued to medical requirements through the abilities of people and the understanding of their bodily, social, mental, intellectual, and purposeful capacity, due to the fact that ultimately it helps the instructor to move an extended way in their training technique and improve their stage and give them plans and skills. As for the research problem, it becomes represented by using the following questions:1. What are the most critical tests that measure the capabilities of emerging handball players?2. Are the skill exams amenable to aggregation into ideal factors and a battery extraction to degree the aptitude for emerging handball players?As for the goals of the research, it is to identify the extent of the overall performance of the simple competencies of emerging handball gamers in Basra Governorate, as well as to outline the easy international construction of the most crucial ability assessments for emerging handball players. As for the studies methods, the researcher, through examining the various assets and analyzing the content of the basic skills and testing them by hand, extracted a set of fundamental competencies and tests from several assets. Therefore, the researcher obtained the ability assessments that pertain to every fundamental skill of the rising players. Through this, a few conclusions emerged, which include1. Simple global creation for basic abilities checks with handball has been decided.A total of four exams were presented, representing the pure factors with the greatest saturation of the primary capabilities checks for handball for emerging gamers.